EFEKTIFITAS METODE PENGAJARAN CARA MENYIKAT GIGI TERHADAP PENURUNAN INDEKS PLAK ANAK USIA 3-5 TAHUN: EFFECTIVITY OF TOOTH BRUSHING TEACHING METHOD IN DECREASING PLAQUE SCORE OF 3-5 YEARS OLD CHILDREN - Hermina; Vera (Dentika: Dental Journal, 2010)
Plaque is the main cause of caries and periodontal disease. Plaque can be cleaned by toothbrushing. Tootbrushing, as all habits of hygiene, can be teachable in the early of childhood because cognitive and motoric abilities can be improved. The aim of this study was to analyse the decreasing plaque indexes among different teaching methods that is with video, demonstration and combination methods. The study design was an experimental pre and post test design. Sixty children from preschool children at Boddhicita school Medan was divided into 4 groups (I-video; II-demonstration; III-combination method ; IV-control group). Plaque control measurement was used with Quigley-Hein index. The results showed that there were significant differences (p<0,05) in decreasing plaque score among the teaching methods (p<0,05). As conclusions, teaching method with combination is more effective in teaching 3-5 years old child than demonstration method. Video method is not recommended in teaching 3-5 years old child.